Phase II Study on Biweekly Combination Therapy of Gemcitabine plus Carboplatin for the Treatment of Elderly Patients with Advanced Non‐Small Cell Lung Cancer - Takayama, Koichi (Oncologist, 2019)
LESSONS LEARNED: The biweekly GEM plus CBDCA dose and schedule showed satisfactory efficacy with mild toxicities in elderly patients with advanced NSCLC. The biweekly GEM plus CBDCA regimen could be considered an alternative to the 3‐week regimen in NSCLC. BACKGROUND: The gemcitabine (GEM)‐carboplatin (CBDCA) combination is widely used for non‐small cell lung cancer (NSCLC) and has some efficacy in elderly patients; however, a high incidence of thrombocytopenia is observed, and the optimal dosage and administration schedules are unknown. This multicenter phase II trial evaluated the efficacy and tolerability of GEM‐CBDCA for elderly patients with chemotherapy‐naive NSCLC. METHODS: Patients with chemotherapy‐naive performance status 0–1 and with stage IIIB/IV NSCLC were administered chemotherapy biweekly (GEM 1,000 mg/m(2) with CBDCA area under the blood concentration‐time curve (AUC) 3 on days 1 and 15 every 4 weeks). The primary endpoint was the objective response rate (ORR), and the secondary endpoints were progression‐free survival (PFS), overall survival (OS), and safety. RESULTS: Forty‐eight patients were enrolled. Median age was 76 years (range, 70–83); 35 patients were men (73%), and 27 patients had adenocarcinoma (56%). The ORR was 29.2% (95% confidence interval [CI], 17.0–44.1). The median PFS, median OS, and 1‐year survival was 5.9 months (95% CI, 4.1–6.6), 13.3 months (95% CI, 8.3–23.5), and 58%, respectively. Grade ≥3 hematological toxicities included neutropenia (29.2%), thrombocytopenia (4.2%), and anemia (20.8%). The incidence of grade ≥3 nonhematological toxicities was <5%. CONCLUSION: This GEM‐CBDCA combination administered biweekly showed satisfactory efficacy with mild toxicities in elderly patients with advanced NSCLC.